1995
DOI: 10.1063/1.114519
|View full text |Cite
|
Sign up to set email alerts
|

Observation of strain effects in semiconductor dots depending on cap layer thickness

Abstract: We have investigated the photoluminescence emission energy of InP dots as a function of cap layer thickness. We find a strong blue-shift with increasing cap layer thickness. The strain tensor in the dot as well as in the surrounding matrix has been modeled using finite element methods and the band gap has been calculated using deformation potential theory. We find good agreement between calculation and experiment. For uncapped dots we find that the emission energy is lower than for biaxially strained InP, and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
34
0

Year Published

1996
1996
2007
2007

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 68 publications
(41 citation statements)
references
References 0 publications
7
34
0
Order By: Relevance
“…6 Similar results have been observed for other systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 and InP/InGaP. 9 We should also consider the contribution of the intermixing at the interfaces, which results in a blue shift. However, a detailed information of the effect of the capping layer on the optical emission of the QDs is still under progress.…”
Section: A Structural Analysissupporting
confidence: 57%
See 2 more Smart Citations
“…6 Similar results have been observed for other systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 and InP/InGaP. 9 We should also consider the contribution of the intermixing at the interfaces, which results in a blue shift. However, a detailed information of the effect of the capping layer on the optical emission of the QDs is still under progress.…”
Section: A Structural Analysissupporting
confidence: 57%
“…Previous studies using uncapped SAQDs have indeed observed weaker photoluminescence ͑PL͒ as compared to capped dots on systems such as InAs/GaAs, 6 InGaAs/GaAs, 7 Ge/Si, 8 and InP/InGaP. 9 In contrast, uncapped InP/GaAs SAQDs present an efficient PL emission that allows us to obtain structural and optical properties from the same sample, which is actually a very important advantage when investigating SAQD properties.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…It has been shown that for coherently grown self-assembled quantum dots the strain state inside the dot depends on the cap layer thickness. 17 In the capped dots the strain in the dots has hydrostatic and biaxial components. The presented dots are not coherently grown and the strain in the buried dots should be more hydrostatic than biaxial, contrary to what has been observed in coherently grown systems.…”
Section: Discussionmentioning
confidence: 99%
“…Light absorption at the E 1 and E 1 1 D 1 critical points of InSb islands buried in InP disappears for nominal InSb thicknesses lower than 10 monolayers as a consequence of the strain produced inside the islands by the cap layer. Certainly, this strain increases as the InSb deposition diminishes, changing the band lineup of the system from type-I to type-II and therefore drastically reducing the oscillator strengths of the island-related E 1 and E 1 1 D 1 transitions.[ S0031-9007(97) [2,3] of islands in self-assembled quantum dot (QD) structures, but also in the physical properties and, in particular, in the optical properties of such systems [4][5][6][7][8]. All previous studies considered only the strain-induced change of the energies of the island-related optical transitions, but strain also modifies the energies of the electronic states of the dots with respect to those of the matrix.…”
mentioning
confidence: 99%